2009
DOI: 10.2320/matertrans.mc200827
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Icosahedral Quasicrystal and Its 1/1 Crystal Approximant in Al-Pd-Sc System

Abstract: An icosahedral quasicrystal (i-phase) and its 1/1 crystal approximant (1/1-phase) have been found to form in Al-Pd-Sc system. The formation areas of the i-phase and the 1/1-phase are limited to very small areas around the compositions of Al 54 Pd 30 Sc 16 and Al 56 Pd 29 Sc 15 , respectively. The valence electrons per atom ratio (e/a ratio) is calculated to be 2.10 for the i-phase of Al 54 Pd 30 Sc 16 . The 16 at% Sc concentration and e=a ¼ 2:10, as well as the intensity profile of the measured X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Moreover, electron diffraction experiments showed that the positions of the diffraction spots slightly deviate from the ideal positions. 18) These results are attributable to the introduction of a phason strain. The i-phase remained unchanged by the annealing at 873 K for 100 h whereas the i-phase transformed to crystalline phase(s) by the annealing at temperatures higher than 973 K. The diffraction intensities and peak widths of the alloy annealed at 873 K were essentially the same as those of the as-solidified alloy.…”
Section: Methodsmentioning
confidence: 82%
See 3 more Smart Citations
“…Moreover, electron diffraction experiments showed that the positions of the diffraction spots slightly deviate from the ideal positions. 18) These results are attributable to the introduction of a phason strain. The i-phase remained unchanged by the annealing at 873 K for 100 h whereas the i-phase transformed to crystalline phase(s) by the annealing at temperatures higher than 973 K. The diffraction intensities and peak widths of the alloy annealed at 873 K were essentially the same as those of the as-solidified alloy.…”
Section: Methodsmentioning
confidence: 82%
“…The formation area of the i-phase is limited to the very narrow composition area around the Al 54 Pd 30 Sc 16 , whereas the formation area of the 1/1-phases is extended along 15 at%Sc line. As discussed previously, 18) 16 at%Sc and e=a ¼ 2:10 are crucially important in the formation of the Tsai-type i-phases. We note that e=a ¼ 2:10 is also important in the formation of the 1/1-phase, although the condition for the 1/1-phase is not much strict in comparison with that for the i-phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The change of crystal structure of rare-earth intermetallic compounds is sometimes seen at the boundary of lighter rare-earth and heavier rare-earth compounds 29) . Phase diagram of the Al-Pd-Sc system is frequently studied because Al54Pd31Sc15 is a wellknown 1/1-crystal approximant to the icosahedral quasicrystal Tsai-type i-phase of the composition Al54Pd30Sc16 30,31) . Detailed study has shown that the approximant phase and i-phase exist in the extremely narrow region of the Al-Pd-Sc phase diagram.…”
Section: Resultsmentioning
confidence: 99%